Subcutaneous Emphysema without Pneumothorax or Pneumomediastinum in Pulmonary Tuberculosis (Journal of Medicine, 2012)
We report a rare case of subcutaneous emphysema without pneumothorax or pneumomediastinum. A 20-year-old gentleman presented with swelling of face and neck, dysphagia and dyspnoea, with the background history of fever, dry cough and weight loss. On examination, there was feeling of crepitus all over the swollen areas, and crackles heard over both lung fields. He had high ESR, with positive Mantoux Test and sputum was positive for AFB. He was put on high concentration oxygen inhalation along with anti-tubercular chemotherapy. Following treatment he was clinically and radiologically improved, and was discharged with the advice to complete the anti-tubercular chemotherapy. DOI: http://dx.doi.org/10.3329/jom.v13i2.12773 J Medicine 2012; 13 : 250-251